Analisis Self Confidence Terhadap Kemampuan Pemahaman Matematis Siswa Sekolah Menengah Atas pada Materi Barisan dan Deret - Allya Rizka Fatimah; Risya Safitri Haryadi; Hamdan Sugilar (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the relationship between students' self-confidence levels and their mathematical understanding of rows and series. The research was conducted using descriptive qualitative method on 30 grade X students in one of the high schools in Bandung Regency. The research data were collected through a mathematical comprehension ability test consisting of five essay questions and a self-confidence questionnaire with four main indicators: confidence in one’s own abilities, acting independently, self-respect, and enthusiasm in discussions. The results showed that students with low self-confidence had an average mathematical understanding score of 18.89, while students with moderate self-confidence had an average of 52.2, and students with high self-confidence had the highest average of 95. This shows that the higher students' self-confidence, the better their ability to understand and solve mathematical problems. This study concludes that self-confidence is one of the important aspects that support students' mathematical understanding ability.